Status of Paliga auratalis (Lepidoptera: Crambidae) as black potato pest and its control strategy using natural enemies - Erniwati; Tiara Sayusti; Woro Anggraitoningsih Noerdjito (Current Research on Bioscences and Biotechnology, 2021)
Plectranthus rotundifolius (Lamiales: Lamiaceae) is an edible tuber that is widely distributed in Asia, covers India, Sri Lanka, Malaysia, and Indonesia. P. rotundifolius which is commonly called black potato in Indonesia is potential to be developed for national food diversification due to its high carbohydrates. However, one of the challenges in black potato cultivation is the existence of leaf-eating caterpillar. This study was aimed to evaluate the status of Paliga auratalis (Lepidoptera: Crambidae) larva as an insect pest in black potato plant and to develop the control strategy by using parasitoid as the natural enemies. Observation and collection of P. auratalis and other potential insect pests were conducted in 12 black potato plantations located in five provinces of Java Island. The life cycle of P. auratalis was observed in the laboratory of Zoology Division, Research Centre for Biology, Indonesian Institute of Science. Rearing of unhealthy P. auratalis larvae was also conducted to observe the parasitoid. We identified five moth larvae species infested black potato plants i.e.: Argyrograma sp., Pycnarmon cribata, Pleuroptya punctimarginalis, Rehimena diemenalis, and Paliga auratalis. Our results showed that P. auratalis larva is the main insect pest in Java Island with the serious attack status and black potato was recorded as a new host plant. Paliga auratalis spend its lifecycle from eggs to adults between 25 – 32 days with the total eggs about 60-80 per female individual. We also identified two parasitic wasps as the parasitoid of P.auratalis i.e.: Cryptopimpla sp. (Hymenoptera: Ichneumonidae) and Aspanteles sp. (Lepidoptera: Barconidae) which are potential to be a biological control agent of P. auratalis